2016
DOI: 10.1002/srin.201600050
|View full text |Cite
|
Sign up to set email alerts
|

Austenite Evolution and Solute Partitioning during Thermal Cycling in the Intercritical Range of a Medium-Mn Steel

Abstract: The evolution of austenite fraction and the associated solute partitioning during the intercritical annealing of medium-Mn steels are of great importance for austenite stabilization and the mechanical performance of this class of steels. In the present work, a 4.5Mn steel is subjected to a cyclic treatment and the evolution of the austenite fraction is measured with dilatometry. The evolution of austenite fraction and solute partitioning are simulated for a case where the starting time of the cyclic treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…It is observed that upon heating in the 2 nd thermal cycle, the volume fraction of δ ferrite in part A-B remains constant, and then gradually increases in part B-C. Therefore, the parts A-B and B-C on the volume fraction curve are referred to as "stagnant" and "forward" stages respectively [10]. During cooling in the 3 rd thermal cycle, the volume fraction of δ ferrite in part C-D continues to increase.…”
Section: Microstructural Analysis Resultsmentioning
confidence: 99%
“…It is observed that upon heating in the 2 nd thermal cycle, the volume fraction of δ ferrite in part A-B remains constant, and then gradually increases in part B-C. Therefore, the parts A-B and B-C on the volume fraction curve are referred to as "stagnant" and "forward" stages respectively [10]. During cooling in the 3 rd thermal cycle, the volume fraction of δ ferrite in part C-D continues to increase.…”
Section: Microstructural Analysis Resultsmentioning
confidence: 99%
“…A local equilibrium (LE) model was often used to simulate the growth kinetics with the solute partitioning. [19,33,[56][57][58] The following Equation ( 3) is assumed in this model, i.e., the chemical potential of each component is equal at the interface in both austenite (γ) and ferrite (α) phases.…”
Section: Reconstructive Transformation Mechanismmentioning
confidence: 99%
“…A local equilibrium (LE) model was often used to simulate the growth kinetics with the solute partitioning. [ 19,33,56–58 ] The following Equation (3) is assumed in this model, i.e., the chemical potential of each component is equal at the interface in both austenite ( γ ) and ferrite ( α ) phases.μiγ*=μiα*where μiγ*and μiα*are the chemical potential of element i ( i = Fe, C, or Mn) at the interface in γ and α, respectively. To study the growth kinetics under this assumption, it is needed to solve Fick's law for all alloying elements{ cijfalse/t=JijJij=Dijcijwhere ∇ is Laplace operator, t is time, and Jij, Dij, and cxj are the diffusion flux, the diffusion coefficient, and the concentration of solute i ( i = C or Mn) in phase j ( j = γ or α ), respectively.…”
Section: Growth Of Austenitic Nucleimentioning
confidence: 99%
“…Medium Mn steels with 3-12 (wt%) alloying element of Mn [1][2][3] have recently been defined as one of the third generations of advanced high-strength steels (AHSSs). Medium Mn steels generally consist of a dual-phase microstructure of ferrite (α) and austenite (γ) at room temperature after intercritical annealing (IA); in that, the addition of Mn to steels can promote the thermal stability of γ.…”
Section: Introductionmentioning
confidence: 99%